A Study Of Absenteeism Among Employees In A Manufacturing Organization - Poh, Kam Hong (2008)
This study examines employee absenteeism in a manufacturing organization. It is a descriptive study where the phenomenon of absenteeism is tried to be explained in the aspect of personal characteristics of the employees.